RELMα-expressing macrophages protect against fatal lung damage and reduce parasite burden during helminth infection - Krljanac, Branislav; Schubart, Christoph; Naumann, Ronald; Wirtz, Stefan; Culemann, Stephan; Krönke, Gerhard; Vöhringer, David (Science immunology, 2019)
Alternatively activated macrophages (AAMs) can contribute to wound healing, regulation of glucose and fat metabolism, resolution of inflammation, and protective immunity against helminths. Their differentiation, tissue distribution, and effector functions are incompletely understood. Murine AAMs express high levels of resistin-like molecule (RELM) α, an effector protein with potent immunomodulatory functions. To visualize RELMα+ macrophages (MΦs) in vivo and evaluate their role in defense against helminths, we generated RELMα reporter/deleter mice. Infection with the helminth Nippostrongylus brasiliensis induced expansion of RELMα+ lung interstitial but not alveolar MΦs in a STAT6-dependent manner. RELMα+ MΦs were required for prevention of fatal lung damage during primary infection. Furthermore, protective immunity was lost upon specific deletion of RELMα+ MΦs during secondary infection. Thus, RELMα reporter/deleter mice reveal compartmentalization of AAMs in different tissues and demonstrate their critical role in resolution of severe lung inflammation and protection against migrating helminths.
CRIS-Team Scopus Importer:2019-06-18